Investigating the control of Concentric and Eccentric Braced Frames against Earthquakes using Viscoelastic dampers - Ali Mohammad Rousta (مهندسی و مدیریت ساخت, 2024)
One of the methods to reduce the earthquake- induced responses in seismic retrofitting of buildings is using dampers. Among different types of dampers, viscoelastic dampers have been proposed as one of the methods of seismic retrofitting of existing structures or seismic design of new buildings in the last two decades. In this research, 3 steel frames of 3, 6 and 10 floors with lateral bearing system of simple braced frame in x direction and flexural frame in y direction were modeled based on edition 4 of standard 2008 in 2000 SAP software and analyzed dynamically and non- linearly based on three earthquake records. These dampers were added to Concentrated Braced Frames and Eccentrically Braced Frame, and the effect of their use in reducing the base shear force was compared. The results showed that viscoelastic dampers in Concentrated Braces had more base shear reduction than in Eccentrically Braces. The results of this study indicate that the reduction of base shear in mid-rise buildings (6 floors) is high and was 66 and 18 and 49 percent respectively in the earthquake records related to Northridge, Kobe and Imperial Valley. On the other hand, the highest energy dissipation of the dampers in 3, 6 and 10 story buildings are related to Kobe earthquake and is 40.78, 60.62 and 38.08%, respectively.